Preparation and characterization of maleic acid grafted chitosan - Hasiploglu, HN; Yilmaz, E; Yilmaz, O; Caner, H (Taylor & Francis Ltd, 2005)
Modification of chitosan (CHI) with maleic acid (MA) via maleic anhydride (MAn) was investigated in acetic acid solution, in the presence of cerium ammonium nitrate (CAN) as the initiator. The effects of reaction time, temperature, and CAN and MA concentrations on the grafting percentage were studied. The products were characterized by Fourier-transform infrared, differential scanning calorimetry, and C-13 NMR, in addition to gravimetric evidence to grafting. A maximum of 105% grafting was achieved under the reaction conditions of 0.12 M CHI, 2.0 M MA, and 0.091 M CAN by stirring for 3 h at 70 degrees C. Dissolution and swelling properties of grafted products were tested in the pH range 3-11. Products up to 36.5% grafting were found to be soluble in aqueous solution, while those with higher grafting percentages (48-81%) were partly soluble in the pH range studied. The product with maximum grafting percentage (105%) swelled and acted as a polyampholyte gel.
Keywords: chitosan; maleic anhydride; cerium ammonium nitrate; water soluble; stimulus responsive